Macrophages as Emerging Key Players in Mitochondrial Transfers - Pang, Yidan; Zhang, Changqing; Gao, Junjie (Frontiers in Cell and Developmental Biology, 2021)
Macrophages are a group of heterogeneous cells widely present throughout the body. Under the influence of their specific environments, via both contact and noncontact signals, macrophages integrate into host tissues and contribute to their development and the functions of their constituent cells. Mitochondria are essential organelles that perform intercellular transfers to regulate cell homeostasis. Our review focuses on newly discovered roles of mitochondrial transfers between macrophages and surrounding cells and summarizes emerging functions of macrophages in transmitophagy, metabolic regulation, and immune defense. We also discuss the negative influence of mitochondrial transfers on macrophages, as well as current therapies targeting mitochondria in macrophages. Regulation of macrophages through mitochondrial transfers between macrophages and their surrounding cells is a promising therapy for various diseases, including cardiovascular diseases, inflammatory diseases, obesity, and cancer.